Influence of habitats on fish assemblages in tropical marine coastal areas of the Southwestern Atlantic - Márcio J. C. A. Lima Júnior; José A. C. C. Nunes; Cláudio L. S. Sampaio (Neotropical Ichthyology)
Abstract In the Southwestern Atlantic, estuarine and marine habitats connect to form biodiverse coastal landscapes. However, the structuring relationships of the assemblages in these landscapes are not yet fully understood. In this context, we sought to investigate the composition of fish assemblages from estuarine and marine habitats: mangroves, artificial structures, sandstone and coral reefs. We also sought to understand the relationship between the assemblages of these habitats by means of similarity. The research was carried out in the RESEX de Jequiá (RXJ) - AL and in Porto Seguro (PTS) - BA, using single Baited Underwater Video (BRUV). At total, 80 samples were taken (40 per location). The coral reef samples stood out significantly, with the greatest richness and abundance at both locations. RXJ had 18% similarity between its habitats, while PTS had 31%, indicating a relationship and the sharing of species in the composition of their assemblages. Sandstone reefs proved to be structural links between mangroves and coral reefs. Additionally, habitat characteristics and depth significantly influence the composition of the assemblages. Here we highlight relevant information for tropical areas little investigated by science in the Southwestern Atlantic, especially with regard to the importance of coastal sandstone reefs.